Parallel developments in Roman law and maritime trade during the Late Republic and Early Principate. (2020) - Candy, Peter
Abstract : Between the Second Punic War and the Early Principate several sources of evidence indicate that the Roman economy experienced some measure of (limited) growth. The case for intensive growth is founded on two complementary approaches. The first has been to construct an "argument from convergence", which observes that several archaeological data-sets, such as Mediterranean shipwrecks, deposits of domestic animal bones at Italian sites and samples of lead and copper pollution from Arctic ice cores and lake sediments, show an increase in chronological distribution during the Late Republic and Early Empire. 1 If taken as proxies for the volume and intensity of exchange, consumption and production, respectively, then, as W. Scheidel has argued, "we may reasonably assume that [these data-sets] indicate at least the general direction of economic development". 2 A second approach has attempted to quantify the GDP of the Roman economy. Although highly conjectural, where such estimates are possible they provide an insight into the trajectory of economic development by giving a rough indication of the rate at which it was probable to have grown or contracted over a given period. 3 P. Kay's "probabilistic quantification" of the GDP of Roman Italy for the 2nd and early 1st c. B.C. 4 concludes that the economy experienced extensive and probably also intensive growth because the rate of inflation remained at a relatively low level. 5 His estimate that prices rose by 95% between 150 and 50 B.C. (i.e., at a compound rate of 0.67% per annum ) accords with the broadly similar conclusions reached by other scholars. 6 Although Kay warns that "the estimates we have produced are assumptions, not facts", the results are both plausible and credible from a comparative perspective. 7